BRETTANOMYCES YEASTS ISOLATED FROM LEBANESE WINES SHOWING DIFFERENCE IN THEIR MOLECULAR PATTERN - Kheir, Joyce; Kallassy, Mireille; Salameh, Dominique; Lteif, Roger; Brandam, Cedric; Strehaiano, Pierre (European Scientific Journal, ESJ, 2014)
The action of Brettanomyces yeast is a leading cause for organoleptic alterations of wine. To evaluate the presence of this yeast in Lebanon, 100 red wine samples selected from 14 wineries located in different regions of the Lebanese territory, were analyzed. Only 3 samples gave positive results. A first PCR showed that all isolates belonged to the species B. bruxellensis. Strains profiles were compared to 2 other French isolates. The PCR-RFLP was then used with 3 endonucleases for an inter-species characterization. The obtained results revealed a degree of polymorphism between strains isolated from different geographical origins. A comparison of the sequence of ITS regions, including the 5.8S rDNA and partial sequences of 18S and 28S rDNA illustrate potential similarities or differences between strains belonging to the same group